Determination of transfer of Azithromycin resistance gene though Conjugation, among Enterobacteriaceae, isolated from Urinary Tract Infected patients - Ferdous, Sharika (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2018.